OP0208 High density fine mapping in rheumatoid arthritis indentifies 14 new loci. (23rd January 2014) - Eyre, S.; Bowes, J.; Diogo, D.; Raychaudhuri, S.; Stahl, E.; Zhernakova, A.; Padyukov, L.; Amos, C.; Plenge, R.; Klareskog, L.; Gregersen, P.; Worthington, J.
Abstract : Background: The advancement in genome wide association studies (GWAS) has brought the number of non-HLA loci associated with RA to 31. There is now the requirement to develop this genetic knowledge and translate it into clinical utility. One of the first steps towards this goal is to fine map these loci to better understand the genetic structure that underpins risk of developing disease. A major finding in the GWAS era has been the overlap of susceptibility loci in autoimmune diseases. This finding, coupled to the requirement to genetically fine map these loci in a wide range of autoimmune diseases, led to a pooling of resources and the development of a custom Illumina array by the Immunochip consortium. Objectives: Fine map the 31 loci already associated with the RA at a genome-wide significance level, as well as investigate whether other novel associations to autoimmune loci on the immunochip array, or with SNPs included as a deep replication of RA GWAS results. Methods: RA and control cohorts were available from 5 countries (UK, USA, Sweden, Spain and The Netherlands).We had 11, 475 cases, of which 7, 222 were ACPA positive (63%) and 3, 339 were ACPA negative, and 15, 870 controls for 163, 081 polymorphic markers.Results of this analysis were added to non-overlapping samples of the previously best powered RA meta analysis to maximise the possibility of revealing novel loci associated with RA (1). Results: We discovered a total of 14 novel RA loci confirmed at genome-wide significance (p<5×10 -8 ), 7 with immunochip data alone and a 7 when the additional GWAS meta analysis was added (Table 1 ), bringing the total of confirmed RA genetic susceptibility loci to 45. Genome-wide significance was also obtained, for the first time, for 2 loci in the ACPA negative analysis, those at HLA (P=2.92×10 -15 ) and ANKRD55 (p=5.18×10 -12 ). Conclusions: Of the 39 confirmed RA loci densely mapped in this study, in more precisely mapping the association signal, we have localised to one gene in the LD defined region for 21 loci and discovered 18 SNPs within exonic regions that are in tight LD with the most associated signal.We present evidence for 14 new loci associated with the susceptibility to RA. These loci continue the theme of RA loci being strongly linked to immune function, and associated with other autoimmune loci. References: Stahl EA, et al. Nat Genet 2010;42:508-14. Disclosure of Interest: None Declared